Hypoglycemic Effect of Betulin in Rats With Experimental Diabetes - Agnieszka Zakrzeska; Paweł Kitlas; Alexej Shlyahtun; Natalia Szymańska; Ryszard Jabłoński; Mikołaj Tomulewicz (Polskie Towarzystwo Farmaceutyczne, 2023)
Betulin is natural pentacyclic triterpenoids lupane-structure, which shows a wide range of biological activity, including possibly hypoglycemic effects. Diabetes mellitus is a metabolic disease, accompanied by chronic hyperglycemia caused by absolute or relative insulin deficiency. The main effective drug in the treatment of type 1 diabetes is insulin injections. In the case of type 2 diabetes, it is an adjuvant therapy. To purpose of this study was to show hypoglycemic action of betulin in a model of experimentally induced diabetes in rats. For the induction of diabetes, alloxan at a dose of 170 mg/kg, i.p. was used. The hypoglycemic effect of betulin was evaluated using doses of 50 and 100 mg/kg/day for 30 days. The activity of glucose metabolism enzymes: liver glycogen phosphorylase, hexokinase and liver and skeletal muscle phosphofructokinase in rats, glucose-6-phosphate dehydrogenase (DG-6-P) of the liver was also evaluated. Betulin in a dose-dependent manner normalized of glycemia, increased the basal insulin concentration in the blood serum, increased the activity of carbohydrate metabolizing enzymes and on the gene expression profile of enzymes involved in carbohydrate metabolism. Betulin also significant improved the morphology of the pancreas. In particular, there was an increase in the area of the islands, their diameter, an increase in the number of β cells in the composition of the islands. We conclude that betulin has hypoglycemic properties, improving glycemia and carbohydrate metabolizing enzymes and pancreatic morphology.